INTEGRATION OF QURBAN VALUES: A HOLISTIC LEARNING MODEL BASED ON ISLAMIC EPISTEMOLOGY - Bilal Abdullah; Zainuddin Zainuddin (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2026)
Abstract This research aims to analyze the integration of the values of qurban in Islamic education through the development of a holistic learning model based on the epistemology of revelation, reason, and experience. The background of this research stems from the problem of the knowledge dichotomy in contemporary Islamic education, which separates the spiritual, rational, and empirical dimensions. The research uses a qualitative approach with a type of bibliographic study (library research) and a philosophical-epistemological analysis of classical literature and recent scientific articles. The results of the research show that Islamic epistemology is integrative in nature, where revelation serves as a source of normative values, reason as a tool for critical analysis, and experience as a means of internalizing values. The worship of the qurban contains comprehensive educational values, which encompass the spiritual, moral, social, and intellectual dimensions. Based on these findings, this research formulates a holistic learning model based on the qurban that integrates the three epistemological dimensions into a single pedagogical framework. This model has significant implications for addressing the knowledge dichotomy, strengthening education in values, as well as increasing the relevance of learning in Islamic Education in the context of real life. This research contributes to the development of an integrative Islamic education paradigm that is not only oriented towards the transfer of knowledge, but also towards the transformation of values and the formation of students' ethical and spiritual consciousness. Keywords: Qurban, Islamic Education, Holistic Learning, Islamic Epistemology, Knowledge Integration